THE HARMONY OF FAMILISM AND FEMINISM IN BIOPIC ON THE BASIS OF SEX - Dewinta, Lia; Naurah, Thifal (CaLLs (Journal of Culture, Arts, Literature, and Linguistics), 2022)
The family is the smallest domain in which patriarchal practices occur, and women become the subjugated object. On the other hand, the biopic film On the Basis of Sex, set in the 1950s, depicts a married couple who mutually support one another. This familism principle, in contrast to the patriarchal principle of the early twentieth century, distinguishes the Ginsburgs as a unique family. The research discussion progresses to how familism is maintained, which resulted in Ruth, the wife's, success in achieving her education and career with the support of her husband. In order to answer the research questions, familism and feminism theories are used. The findings show that the couple prioritizes family over self-interest because they value family interconnectedness; they believe family as source of emotional support; they want to maintain family honor; they want to obtain family benefit; and they want to fulfil family obligations. The idealism leads them to the practice of feminism, which takes place both in the domestic and public spheres. As a result, it was found that strong family bonds can be used to break the patriarchal tradition by implementing feminist practices.